Towards a Reference Model for Grassroots Enterprise Mashup Environments - Hoyer, Volker; Stanoevska-Slabeva, Katarina (My University, 2009)
A new kind of Web-based application, known as Enterprise Mashups, has gained momentum in the last years: Business users with no or limited programming skills are empowered to leverage in a collaborative manner user friendly building blocks and to combine and reuse existing Web-based resources within minutes to new value added applications in order to solve an individual and ad-hoc business problem. Current discussions of the Mashup paradigm in the scientific community are limited on technical aspects. The collaboration and the peer production management aspects of the Mashup development have received less attention yet. In this paper, we propose a reference model for Enterprise Mashups which provides a foundation to develop and to analyse grassroots Enterprise Mashup environments from a managerial and collaborative perspective. By following the design science research approach, we investigate existing reference models and leverage the St. Gallen Media Reference Model (MRM). The development of Enterprise Mashups is structured by market transaction phases similar to electronic markets. The user roles, the necessary processes and the resulting services are modelled according to the views of the MRM. By means of the SAP Research RoofTop Marketplace prototype we demonstrate the application of the designed reference model for grassroots Enterprise Mashups environments. WINNER OF THE BEST PAPER AWARD. http://www.ecis2009.it